Lateral load bearing capacity of offshore high-piled wharf with batter piles. (15th September 2017) - Xie, Yaofeng; Liu, Chenglin; Gao, Suyang; Tang, Jieping; Chen, Yan
Abstract: Understanding the lateral load behavior of high-piled wharf is of practical value to structural design, and the horizontal load bearing capacity of the bent is essential to analyzing the behavior of the high-piled wharf. In this paper, finite element models of high-piled wharf are built in a general finite element software–ANSYS to investigate the lateral loading behavior. Parametric analyses have been performed on the working behavior of single pile with varying slopes and section sizes under different load levels. The behavior of bent with batter piles under different lateral loads is discussed. The formulas of lateral load vs. horizontal displacement for single pile and high-piled wharf are formulated and presented in this paper. The numerical simulation results of pile top displacement are found to be in good agreement with those predicted using the theoretical formula presented in this paper. These formulas, which describe the relationship between top displacement and stiffness, inclination and loads, can be useful to determine the horizontal load bearing capacity of the high-piled wharf with batter piles and can realize the real-time safety monitoring of the high-piled wharf for practical application. Highlights: Build the simulation models of the pile-supported platform with ANSYS. Formulas of single pile and pile-supported platform force-displacement are proposed. Reveal the relationship between the top displacement, stiffness, inclinations and loads.